Innovation in Scad Mackerel (Decapterus spp.) Processing Into Economically Valuable Products for Improving The Skills of Coastal Communities in Nambo Village - Sitti Wirdhana Ahmad; Nur Arfa Yanti; Muhsin Muhsin; Andi Septiana; Muzuni Muzuni; Taufik Walhidayah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Scad Mackerel (Decapterus spp.) is the main consumption commodity of coastal communities in Nambo village. Apart from public awareness is quite high, the price is affordable, and has nutritional value since unsaturated fats is low, so it good to consume for all ages. The public lack of knowledge about proper fish management. The solution is to provide an understanding of fish processing techniques so be more selling, delicious and nutritious, as well as for community empowerment with the aim of creating fisheries entrepreneurs. The method was the lecture method, socialization and training to the community as an empowerment effort to improve knowledge, skills and well-being. The implementation of the service in the form of location surveys, coordination with local regional chief of village and PKK administrators, preparation of equipment and materials, and some processed samples of fish, socialization about the benefits of fish and fish processing training